The Effectiveness of Case Method-Based Teaching Modules on Ecosystem Materials to Enhance Learning Outcomes of Fifth Grade Elementary School Students - Shanti Andria Chairani; Fauziyah Harahap; Rachmat Mulyana (Didaktika: Jurnal Kependidikan, 2024)
The purpose of this study was to determine the effectiveness of the case method-based teaching module on ecosystem material in improving science learning outcomes of grade V students of SDN 107103 Lantasan Baru which is adjusted to the independent learning curriculum. This study is a type of research and development (Reasearch and Development) using the 4D model (define, design, develop, disseminate). The results of the study showed that the pre-test and post-test results showed an increase in the average learning outcome score of 29.3. The initial pre-test results showed an average student score of 54.7 and the post-test results showed an increase in the average class score of 84. Therefore, it can be concluded that the case method-based teaching module on ecosystem material can be categorized as effective in improving science learning outcomes of grade V students.